Development of a Low-NOx Fuel-Flexible and Scalable Burner for Gas Turbines - Antonio Di Nardo; Eugenio Giacomazzi; Matteo Cimini; Guido Troiani; Silvera Scaccia; Giorgio Calchetti; Donato Cecere (Energies)
To reduce dependence on fossil fuels, gas turbine plants using hydrogen/methane blends provide a crucial solution for decarbonizing thermal power generation and promoting a sustainable energy transition. In this context, the development of fuel-flexible burners is fundamental. This work reports the development of a novel burner geometry for gas turbines that can operate with natural gas and hydrogen mixtures (HENG, hydrogen-enriched natural gas) over a wide range of hydrogen content while maintaining low NOx emissions. The methodology used in this work is multidisciplinary, incorporating (i) CFD numerical simulations to determine the burner’s geometry, (ii) mechanical design for prototype construction (not discussed in the article), and (iii) experimental tests to assess its hydrogen content capacity, stabilization, and pollutant emission characteristics. The geometry was initially optimized through several RANS simulations to enhance reactant mixing and minimize flashback risks. Additionally, some LES simulations were conducted under specific conditions to achieve more accurate predictions and investigate potential combustion dynamics issues. The proposed solution was then transferred into a prototype. Through experimental testing, the burner prototype was characterized in terms of four key performance indicators: (1) the ability to operate with HENG mixtures with more than 20% <semantics>H2</semantics> content, showing a technological trend exceeding 50%; (2) the ability to operate with low <semantics>NOx</semantics> (<25 ppm) and CO emissions within the 30–70% hydrogen volume range; (3) the ability to ignite HENG mixtures with <semantics>H2</semantics> in the 30–70% hydrogen volume range; and (4) the ability to operate with a fluctuating hydrogen content, ±15% over time, while still complying with <semantics>NOx</semantics> and CO emission limits.